DNA sequencing analysis of cystic fibrosis transmembrane conductance regulator gene identifies cystic fibrosis‐associated variants in the Severe Asthma Research Program. Issue 7 (5th May 2022) - Izquierdo, Manuel E.; Marion, Chad R.; Moore, Wendy C.; Raraigh, Karen S.; Taylor‐Cousar, Jennifer L.; Cutting, Gary R.; Ampleford, E.; Hawkins, Gregory A.; Zein, Joe; Castro, M.; Denlinger, Loren C.; Erzurum, Serpil C.; et al.
Abstract: Background: Heterozygote carriers of potentially pathogenic variants in the cystic fibrosis transmembrane conductance regulator ( CFTR ) gene have increased asthma risk. However, the frequency and impact of CFTR variation among individuals with asthma is unknown. Objective: To determine whether potentially pathogenic CFTR variants associate with disease severity and whether individuals with two potentially pathogenic variants exist in a severe asthma‐enriched cohort. Methods: We analyzed sequencing data spanning a 190.5Kb region of CFTR in participants from the Severe Asthma Research Program (SARP1‐3). Potentially pathogenic, rare CFTR variants (frequency < 0.05) were classified as CF‐causing or of varying clinical consequences (VVCC) (CFTR2. org). Regression‐based models tested for association between CFTR genotypes (0‐2 potentially pathogenic variants) and severity outcomes. Results: Of 1401 participants, 9.5% (134) had one potentially pathogenic variant, occurring more frequently in non‐Hispanic white (NHW, 10.1% [84 of 831]) compared to African American individuals (AA, 5.2% [22 of 426]). We found ≥2 potentially pathogenic CFTR variants in 1.4% (19); 0.5% (4) of NHW and 2.8% (12) of AA. Potentially pathogenic CFTR variant genotypes (≥1 or ≥2 variants) were not cumulatively associated with lung function or exacerbations. In NHW, we found three F508del compound heterozygotes with F508del and a VVCC (two 5 T; TG12[c.1210‐11 T > G] and one Arg1070Trp) and a homozygote for the VVCC, 5 T; TG12. Conclusions: We found potentially pathogenic CFTR variants within a severe asthma‐enriched cohort, including three compound heterozygote genotypes variably associated with CF in NHW individuals. These findings provide the rationale for CFTR sequencing and phenotyping of CF‐related traits in individuals with severe asthma.